Sosialisasi Internet Sehat, Cerdas, Kreatif dan Produktif di Era Pandemi COVID 19 pada MA NW Tanak Maik Masbagek - Muhammad Innuddin; Dedy Febry Rahman; Hairani Hairani; Andi Sofyan Anas; Hasbullah Hasbullah (LPPM Universitas Bumigora, 2022)
Healthy, Smart, Creative and Productive Internet in the Era of the Covid 19 Pandemic. The research objectives include: to find out how to use the technology and describing how to use technology properly to reduce negative impacts. This research method is a descriptive qualitative method. The techniques used in collecting data are observation techniques, interview techniques, and documentation. The results of this study found two problems, including 1) did not understand how to use and utilize internet technology properly, 2) lack of teacher evaluation and control on students. The conclusion of this research is the use and utilization of technology properly, leading to positive impacts and reducing negative impacts. By knowing how to use internet technology properly and correctly, it will be able to make students smart, creative, and productive. The purpose of being intelligent, creative, and productive is that students can develop and apply what has been obtained in internet technology, which is applied in their daily lives, both within the school environment or outside the school environment.